Impact of Viruses on Prokaryotic Communities and Greenhouse Gas Emissions in Agricultural Soils - Xing Huang; Lucas P. P. Braga; Chenxiao Ding; Bokai Yang; Tida Ge; Hongjie Di; Yan He; Jianming Xu; Laurent Philippot; Yong Li (Advanced Science)
Abstract Viruses are abundant and ubiquitous in soil, but their importance in modulating greenhouse gas (GHG) emissions in terrestrial ecosystems remains largely unknown. Here, various loads of viral communities are introduced into paddy soils with different fertilization histories via a reciprocal transplant approach to study the role of viruses in regulating greenhouse gas emissions and prokaryotic communities. The results showed that the addition of viruses has a strong impact on methane (CH4) and nitrous oxide (N2O) emissions and, to a minor extent, carbon dioxide (CO2) emissions, along with dissolved carbon and nitrogen pools, depending on soil fertilization history. The addition of a high viral load resulted in a decrease in microbial biomass carbon (MBC) by 31.4%, with changes in the relative abundance of 16.6% of dominant amplicon sequence variants (ASVs) in comparison to control treatments. More specifically, large effects of viral pressure are observed on some specific microbial communities with decreased relative abundance of prokaryotes that dissimilate sulfur compounds and increased relative abundance of Nanoarchaea. Structural equation modeling further highlighted the differential direct and indirect effects of viruses on CO2, N2O, and CH4 emissions. These findings underpin the understanding of the complex microbe‐virus interactions and advance current knowledge on soil virus ecology.